Quantification of green space landscape structure for sustainable land use planning in Pasir Mas, Kelantan - Nur Aimi Zafirah Md. Akkir (2019)
Globally, rapid urban expansion has caused a significant decline of green spaces in the urban areas. Urbanization can lead to the variation of the spatial structure and causes serious changes in term of the landscape ecological function. This study intends to fill the gap in knowledge to reveal the land use components as networks of social area also the spatial structure and pattern of green space. The research objectives are to quantify the landscape changes of urban expansion and green space area of year 1994, 2004, and 2014 in Pasir Mas, Kelantan and to determine the landscape structure pattern of urban expansion and green space of year 1994, 2004, and 2014 in Pasir Mas, Kelantan. The method that has been used is the landscape change, landscape structure and statistical analysis by using the software such as ERDAS Imagine, ArcGIS, FRAGSTAT and SPSS. Three raw satellite images were extracted for year 1994, 2004 and 2014. The classification of land use land cover (LULC) was based on five types of the area which are forest, agriculture area, cleared land, water bodies and built-up area. This study resulting in the changes between the percentages of area for every class. For Pasir Mas district the highest percentage of area is agriculture while water bodies are the lowest among five classes. Six metrics for landscape structure analysis were selected such as Euclidean nearest neighbour distance (MNN), mean patch area (MPA), patch density (PD), landscape shape index (LSI), percentage of area (PAREA), and largest patch index (LPI) in order to represent the changes of characteristics such as patch isolation, shape and size in green space landscape. In a nutshell, this study will aid the understanding to provide the first and latest statistical representation of data tracking of urban expansion in Pasir Mas, Kelantan by using GIS and remote sensing application in order to produce the land use map as the final output.